N‐Methyl‐D‐Aspartate Receptor Antibodies in Autoimmune Encephalopathy Alter Oligodendrocyte Function. Issue 5 (24th February 2020) - Matute, Carlos; Palma, Ana; Serrano‐Regal, María Paz; Maudes, Estibaliz; Barman, Sumanta; Sánchez‐Gómez, María Victoria; Domercq, María; Goebels, Norbert; Dalmau, Josep
Abstract : Objective: Antibodies against neuronal N‐methyl‐D‐aspartate receptors (NMDARs) in patients with anti‐NMDAR encephalitis alter neuronal synaptic function and plasticity, but the effects on other cells of the nervous system are unknown. Methods: Cerebrospinal fluid (CSF) of patients with anti‐NMDAR encephalitis (preabsorbed or not with GluN1) and a human NMDAR‐specific monoclonal antibody (SSM5) derived from plasma cells of a patient, along the corresponding controls, were used in the studies. To evaluate the activity of oligodendrocyte NMDARs and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors in vitro after exposure to patients' CSF antibodies or SSM5, we used a functional assay based on cytosolic Ca 2+ imaging. Expression of the glucose transporter (GLUT1) in oligodendrocytes was assessed by immunocytochemistry. Results: NMDAR agonist responses were robustly reduced after preincubation of oligodendrocytes with patients' CSF or SSM5 but remained largely unaltered with the corresponding controls. These effects were NMDAR specific, as patients' CSF did not alter responses to AMPA receptor agonists and was abrogated by preabsorption of CSF with HEK cells expressing GluN1 subunit. Patients' CSF also reduced oligodendrocyte expression of glucose transporter GLUT1 induced by NMDAR activity. Interpretation: Antibodies from patients with anti‐NMDAR encephalitis specifically alter the function of NMDARs in oligodendrocytes, causing a decrease of expression of GLUT1. Considering that normal GLUT1 expression in oligodendrocytes and myelin is needed to metabolically support axonal function, the findings suggest a link between antibody‐mediated dysfunction of NMDARs in oligodendrocytes and the white matter alterations reported in patients with this disorder. ANN NEUROL 2020;87:670–676